Pengembangan Potensi di Bidang Ekonomi, Hukum, dan Pendidikan Pada Masjid Nurul Huda Komplek Taman Kedaung Pamulang Tangerang Selatan (Sub Bidang :Baitul Mal, Sekolah, dan LBH) - Muhammad Rizal Saragih; Sujarwo Sujarwo; Rusdi Rusdi; Mawardi Nurullah; Prima Sadewa (S1 Accounting Program, Universitas Pamulang, 2020)
The purpose of this community service is to provide knowledge and understanding of Baitul Mal, Legal Aid Institutions, and improve the quality of schools. This method of community service is seminars and discussions. The population in this community service activity is as many as 50 people who are managers and residents of Taman Kedaung, South Tangerang. The result of this community service is that all participants can establish Baitul Mal, a Legal Aid Institute, and improve the quality of schools at the Nurul Huda Mosque.